Evaluation of Risk Factors Affecting on Oil and Gas Construction Projects in Yemen - A. Kassem, Mukhtar; Azry Khoiry, Muhamad; Hamzah, Noraini (International Journal of Engineering and Technology, 2019)
Risk factors are unique in every of the construction projects are facing today. This research is conducted to identify and assess the relative importance of the significant risk factors contributing to cost and time overrun in oil and gas construction project in Yemen. Usually, construction projects affected by risk factors during the project lifecycle, without identifying and classify of this risks the project cannot be succeeded, in this paper, the project players, i.e. clients, contractor, consultant, project managers and engineers are taken for a survey to obtain the impact and probability of risk factors. The research aimed to identify the principal risks which effect on success of construction projects, to set the correct risk respond we should know the ranking of risks base on its impact and probability of occurs, in this paper we will use relative important index method (RII) and Spearmanâ€™s rank correlation between the risks for analysis questionnaire responses. As a result of the research, external risk factors are the most influential in the oil sector construction projects in Yemen and project management risk factors are the most influential among the internal risk factors.Â